Kesan Rawatan Melalui Suntikan Ke Atas Puasa Pesakit - Mat, Hamidah; Ab Ghani, Anisah (Jurnal Fiqh, 2012)
This article aims to discuss the effects of treatment by injection on the rule of fasting. Previously, the issue of treatment has been the subject of debate among the fuqaha in assessing the impact of treatment on the ruling of fasting patients. This is because the medical treatment, which involves the insertion of something into acavity of the body has been considered nullified by the majority of fuqaha in the past. Also discussed are the basic principles underlying the assessment that can be applied to the assessment of the impact of other treatment methods on the ruling of fasting patients.This article is based on both library and field research. The library research focuses on collecting and analysing all the related information from both fiqh and the medical point of view. While the field research involved interviews with medical officers. This article found that treatments by injection are not considered as nullifiers of fasting except for the injections of food or drink in to the body.